Future-mindedness pada gelandangan dan pengemis yang menjalani rehabilitasi - Nurchayati, Nurchayati; Rizqiyah, Aulia Rachmah (Mediapsi, 2023)
Homelessness and beggary are social problems, particularly for urban community. The Indonesian government has long used rehab centers to train vagrants and beggars to be fully functioning members of society. Future-mindedness is one of the life-attitudes that the homeless and beggars are to learn to adopt. Using the case study approach, this qualitative psychological research explores future-mindedness among vagrants and beggars undergoing rehab programs. Data were collected through semi-structured interviews with four participants and two of their significant others. The thematic analysis conducted on the interview data produced three key findings: a) the circumstances that had helped bring about beggary and vagrancy; b) the ways the beggars and vagrants learned to plan their lives; and c) the factors that enabled them to think about the future. This study concludes that employment, place of residence, and family life formed the center of these people’s future plans. Rehab programs—if they are to succeed—must take into account both the personal context and the social environment in which beggars and vagrants have lived their lives and are learning to re-think their futures.